Tracing the history of clinical practice of liquid biopsy: a bibliometric analysis - Zhang, Shuo; Zhao, Hongwei; Wang, Kangchun; Li, Lijie; Pan, Qi; Lu, Meitong; Zhang, Xing (Frontiers in Immunology, 2025)
IntroductionLiquid biopsy holds great promise in clinical diagnosis, treatment, and prognostic monitoring. This study reveals the development of liquid biopsy in clinical practice through a comprehensive bibliometric analysis.MethodsA total of 40 years of research literature in this field was included from the Web of Science Core Collection (WoSCC), analyzing the evolving research trends of liquid biopsy in clinical practice. We constructed co-occurrence networks for countries, institutions, authors, and keywords, integrating citation analysis and journal impact metrics to provide a comprehensive view of the research landscape in the field of liquid biopsy.ResultsThe results show a significant growth trend in the clinical practice of liquid biopsy, with China and the United States being the leading contributors. Institutions such as Harvard University and the University of California system play a central role in the global collaboration network. Cancers has become the primary publication outlet for the field, while highly cited journals like Clinical Cancer Research play a crucial role in advancing its development. Keyword analysis reveals that research has progressively expanded into clinical applications, personalized treatment, and prognostic evaluation.DiscussionOverall, as technology and applications continue to mature, liquid biopsy is expected to play an even greater role in the early diagnosis, treatment evaluation, and personalized treatment of cancer and other diseases.